Technology Use Analysis for Administrative Assistants by Using The Theory of Technology Acceptance Model - Maria Francisca Lies Ambarwati (Jurnal Administrasi dan Kesekretarisan, 2021)
Working behaviour has changed because of the unprecedented condition of the Covid-19 pandemic. People manage to find new ways of doing their work from their houses with the help of technology. Using the concept of Theory of Technology Acceptance Model (TAM), the purpose of this study was to reveal the perception of secretaries, administrative assistants, and administrative staffs in carrying out their administrative work during the Covid-19 pandemic. By conducting in depth interview on 15 secretaries, administrative assistants, and administrative staffs, this qualitative case study method was used to obtain information about the constraints and consequences of the Covid-19 pandemic on the interviewees. The findings of this study revealed that the 15 secretaries, administrative assistants, and administration staffs could perceive the ease of use of and the usefulness of technology in supporting their work during the Covid-19 pandemic. The result showed that technology supported the interviewees in doing their administrative work and eliminated the delay in time as they could execute and finish the work in time and maintain their good performance in working. It is recommended that organizations should provide their secretaries with sufficient trainings in modern technology and equipment usage to upgrade and enhance their skills and competencies in technological advancement. The limitations of this study laid in the age and gender of the interviewees.